Human Chorionic Gonadotropin and Breast Cancer - Schüler-Toprak, Susanne; Treeck, Oliver; Ortmann, Olaf (International journal of molecular sciences, 2017)
Breast cancer is well known as a malignancy being strongly influenced by female steroids. Pregnancy is a protective factor against breast cancer. Human chorionic gonadotropin (HCG) is a candidate hormone which could mediate this antitumoral effect of pregnancy. For this review article, all original research articles on the role of HCG in breast cancer were considered, which are listed in PubMed database and were written in English. The role of HCG in breast cancer seems to be a paradox. Placental heterodimeric HCG acts as a protective agent by imprinting a permanent genomic signature of the mammary gland determining a refractory condition to malignant transformation which is characterized by cellular differentiation, apoptosis and growth inhibition. On the other hand, ectopic expression of β-HCG in various cancer entities is associated with poor prognosis due to its tumor-promoting function. Placental HCG and ectopically expressed β-HCG exert opposite effects on breast tumorigenesis. Therefore, mimicking pregnancy by treatment with HCG is suggested as a strategy for breast cancer prevention, whereas targeting β-HCG expressing tumor cells seems to be an option for breast cancer therapy.